Pesantren dan Politik: Meneguhkan Identitas Majelis Pesantren Salafiyah (MPS) Banten - Rohman albantenologi (Laboratorium Bantenologi UIN Sultan Maulana Hasanuddin Banten, 2020)
This article describes and analyzes the emergence of a Salafiyah (traditional) Islamic boarding school organization called Salafiyah Islamic Boarding School (Majelis Pesantren Salafiyah/MPS). This organization plays an important role in its efforts to bring out the role of Salafiyah Islamic boarding schools in the political context at the local and national levels. Some of the political momentum carried out by MPS includes organizing Salafiyah Islamic boarding school kyai in the Baros area (Serang district) and Cadasari (Pandeglang district) in advocating and fighting against national company suspected of destroying the water sources needed by residents in the area of Serang and Pandeglang districts, struggling for the Islamic boarding school regulation through the parliament of Banten Province, involving practically in the 2014 and 2019 Presidential Elections, and helping the government to decrease the 212 movement influence in Banten. The research results show that the emergence of MPS is a form of resistance identity, namely an identity that is created by actors who are marginalized or stigmatized by the logic of domination who then build channels of resistance and defense based on the principles of difference from or contrary to existing social institutions.